A Novel Orthotopic Implantation Technique for Osteosarcoma Produces Spontaneous Metastases and Illustrates Dose-Dependent Efficacy of B7-H3-CAR T Cells - Talbot, Lindsay Jones; Chabot, Ashley; Funk, Amy; Nguyen, Phuong; Wagner, Jessica; Ross, Aaron; Tillman, Heather; Davidoff, Andrew; Gottschalk, Stephen; DeRenzo, Christopher (Frontiers in Immunology, 2021)
The outcome for metastatic pediatric osteosarcoma (OS) remains poor. Thus, there is an urgent need to develop novel therapies, and immunotherapy with CAR T cells has the potential to meet this challenge. However, there is a lack of preclinical models that mimic salient features of human disease including reliable development of metastatic disease post orthotopic OS cell injection. To overcome this roadblock, and also enable real-time imaging of metastatic disease, we took advantage of LM7 OS cells expressing firefly luciferase (LM7.ffLuc). LM7.ffLuc were implanted in a collagen mesh into the tibia of mice, and mice reliably developed orthotopic tumors and lung metastases as judged by bioluminescence imaging and histopathological analysis. Intratibial implantation also enabled surgical removal by lower leg amputation and monitoring for metastases development post-surgery. We then used this model to evaluate the antitumor activity of CAR T cells targeting B7-H3, an antigen that is expressed in a broad range of solid tumors including OS. B7-H3-CAR T cells had potent antitumor activity in a dose-dependent manner and inhibited the development of pulmonary metastases resulting in a significant survival advantage. In contrast T cells expressing an inactive B7-H3-CAR had no antitumor activity. Using unmodified LM7 cells also enabled us to demonstrate that B7-H3-CAR T cells traffic to orthotopic tumor sites. Hence, we have developed an orthotopic, spontaneously metastasizing OS model. This model may improve our ability not only to predict the safety and efficacy of current and next generation CAR T cell therapies but also other treatment modalities for metastatic OS.